General practice registrar responses to the use of different risk communication tools in simulated consultations: a focus group study. Issue 7212 (18th September 1999) - Edwards, Adrian; Elwyn, Glyn; Gwyn, Richard
Abstract: Objectives: To pilot the use of a range of complementary risk communication tools in simulated general practice consultations; to gauge the responses of general practitioners in training to these new consultation aids. Design: Qualitative study based on focus group discussions. Setting: General practice vocational training schemes in South Wales. Participants: 39 general practice registrars and eight course organisers attended four sessions; three simulated patients attended each time. Method: Registrars consulting with simulated patients used verbal or "qualitative" descriptions of risks, then numerical data, and finally graphical presentations of the same data. Responses of doctors and patients were explored by semistructured discussions that had been audiotaped for transcription and analysis. Results: The process of using risk communication tools in simulated consultations was acceptable to general practitioner registrars. Providing doctors with information about risks and benefits of treatment options was generally well received. Both doctors and patients found it helped communication There were concerns about the lack of available, unbiased, and applicable evidence and a shortage of time in the consultation to discuss treatment options adequately. Graphical presentation of information was often favoured—an approach that also has the potential to save consultation time. Conclusions: A range of risk communication "tools" with which to discuss treatment options is likely to be more applicable than a single new strategy. These tools should include both absolute and relative risk information formats, presented in an unbiased way. Using risk communication tools in simulated consultations provides a model for training in risk communication for professional groups.